Synthesis and Characterization of 4-Aroyl Substituted Pyrazoline - V. Tekade, Pradip; Patil, K.N.; Bodkhe, P.S. (Asian Journal of Chemistry, 2016)
New 4-aroyl substituted pyrozoline (II) have been synthesized by the condensation of Ph·NH–NH2·HCl with 3-aroyl flavanone (I) in DMF containing small amount of piperidine. Structure of the compound has been characterized by melting point, TLC, IR and PMR spectra.